A strategy of functional crosslinking acellular matrix in blood-contacting implantable devices with recombinant humanized collagen type III (rhCOLIII). (1st April 2022) - Ge, Yao; Guo, Gaoyang; Liu, Kunpeng; Yang, Fan; Yang, Li; Wang, Yunbing; Zhang, Xingdong
Abstract: A large number of blood contacting implantable devices are used worldwide annually. Acellular matrix (AM), as one of the blood-contacting materials, has achieved a great success, since it remains the structures, components and certain functions of extracellular matrix. However, AM often fails during the period of service owing to non-ideal anticoagulation, severe inflammatory responses and poor mechanical properties. Herein, we specially prepared a newly designed tailored recombinant humanized collagen type III (rhCOLIII) that effectively removed the binding site to platelets while retaining cytocompatibility. In this study, a radical-polymerization-crosslinked decellularized porcine pericardium (DPP) with rhCOLIII and glycidyl methacrylate (GMA) through one-pot method was designed as artificial heart valves. Due to the introduction of rhCOLIII, the anticoagulation properties were dramatically improved with fewer platelets adhesion and less thrombogenesis. The mechanical properties of the novel heart valve (rhCOLIII/GMA-DPP) were significantly enhanced through radical polymerization crosslinking. Furthermore, experiments in vivo and vitro showed the inflammatory responses were moderately reduced. In conclusion, this study provides a simple strategy for functional crosslinking AM in blood-contacting implantable devices and shows possibilities for real application. Graphical abstract: Image 1 Highlights: rhCOLIII possess both affinity for endothelial cells and anticoagulation property. A simply radical polymerization crosslinking method for acellular matrix. Functional crosslinked acellular matrix with rhCOLIII performs well as heart valves.